Moby Dick - Melville, Herman, 1819-1891 (Boston, Mass. : Thomson Heinle, 2005)
A terrible tragedy to tell the classic tale of Captain Ahab's (Gregory Peck) obsessive hunt for the great white whale that has dictated his destiny ever since leaving him a peg-legged cripple. In a perilous journey that will take Ahab and his crew to the ends of the Earth, no sacrifice is too great in Ahab's thirst for bloody revenge
Title from container
Keywords: Ahab, Captain (Fictitious character) -- Fiction; Whaling ships -- Fiction; Ship captains -- Fiction; Mentally ill -- Fiction; Shipwrecks -- Fiction